Physical properties of Nanostructured ZnO Thin Films deposited by DC magnetron Sputtering method with Different volume of O2 in Carrier gas - Asgary, somayeh; ramezani, amir hoshang; mahmoodi, azam (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
High-quality crystals of ZnO thin films with polycrystalline hexagonal structure and (101) preferentially oriented were deposited on Si and corning glass substrates by reactive DC magnetron sputtering. The effects of different amount of oxygen in carrier gas on the structural, morphological and optical properties have been investigated. Increasing of O2 amount resulted in decreasing of intensity of preferred orientation and peak shifting to lower 2θ values. Scanning electron microscopic images showed a porous tapered columnar structure similar to the zone 1 of Thornton’s structure zone model at lower O2 content and a smooth microstructure similar to the zone T structure at highest O2 content. AFM images showed that film morphology and surface roughness were influenced by O2 concentration. UV-Vis-NIR measurements indicated that the absorbance increases and shifts to shorter wavelength (blue shift) at higher O2 content. With increasing O2 amount, the optical band gap increases from 3.3 to 3.8 eV.